POS 데이터를 이용한 우유 수요 분석 - 신승열 (한국농촌경제연구원, 2003)
Analysis of Milk Demand with POS Data This paper constitutes a trial of using scanner data (POS data) to estimate demand for milk (white milk, fortified milk, low-fat milk, flavored milk, children's milk) using linear approximation/almost ideal demand system (LA/AIDS). The databases were taken from various (five different marketing channels) retail stores across the country that account for approximately 5 percent of Korean retail sales. Own-price elasticities are negative and most milk products are statistically significant in elastic range except low-fat milk. Cross-price effects are marginal, and statistically significant between white milk and fortified, flavored milk. Advertising effects are marginal, and statistically significant except flavored milk. Seasonality is apparent from July through September except children's milk. This paper demonstrate the possibility of using scanner data in analyzing Korean food demand. Researchers: Shin Seung-Youll and Jeong Min-Kook E-mail address: ysshin@krei.re.kr
Keywords: POS데이터 우유수요분석 우유제품 우유소비